Bolchevik cinema: a benjaminian analysis of soviet cinema of the stalinist period (Research, Society and Development, 2022)
Cinema is a source that is often “marginalized” by historiography in general. In this sense, this article seeks to establish an analysis of the Soviet regime in the Stalinist period (1924-1953), considered the moment of toughest repression of the opposition of the Soviet Union, through its cinematographic productions and sources. Since the country, like other nations, invested heavily in the film industry, in order to use it as a form of political propaganda, disseminating its ideologies. The work of art in the era of its technical reproducibility, by the German philosopher Walter Benjamin, was used as the main theoretical reference, mainly the concepts of “aestheticization of politics” and “politicization of art”. In the book, the author analyzes, in general terms, the art scene at the beginning of the 20th century, when new technologies such as cinema and the camera revolutionized the way art was produced and consumed. Benjamin, therefore, does not make a specific analysis of Soviet cinematographic productions, but even so, his analyzes are applicable to the Soviet context. It is concluded throughout this article that Soviet cinema has a revolutionary “soul” in the 1920s, placing the proletariat as the protagonist. However, over the years and the consolidation of Stalin's dictatorship, the proletariat lost its protagonism to the "great heroes" of the Bolshevik party, bringing Soviet cinema closer to the bourgeois cinema that Benjamin so criticized.